[111In]In/[177Lu]Lu-AAZTA5-LM4 SST2R-Antagonists in Cancer Theranostics: From Preclinical Testing to First Patient Results - Berthold A. Nock; Panagiotis Kanellopoulos; Euy Sung Moon; Maritina Rouchota; George Loudos; Sanjana Ballal; Madhav P. Yadav; Chandrasekhar Bal; Prashant Mishra; Parvind Sheokand; Frank Roesch; Theodosia Maina (MDPI AG, 2023)
Aiming to expand the application of the SST2R-antagonist LM4 (DPhe-c[DCys-4Pal-DAph(Cbm)-Lys-Thr-Cys]-DTyr-NH2) beyond [68Ga]Ga-DATA5m-LM4 PET/CT (DATA5m, (6-pentanoic acid)-6-(amino)methy-1,4-diazepinetriacetate), we now introduce AAZTA5-LM4 (AAZTA5, 1,4-bis(carboxymethyl)-6-[bis(carboxymethyl)]amino-6-[pentanoic-acid]perhydro-1,4-diazepine), allowing for the convenient coordination of trivalent radiometals of clinical interest, such as In-111 (for SPECT/CT) or Lu-177 (for radionuclide therapy). After labeling, the preclinical profiles of [111In]In-AAZTA5-LM4 and [177Lu]Lu-AAZTA5-LM4 were compared in HEK293-SST2R cells and double HEK293-SST2R/wtHEK293 tumor-bearing mice using [111In]In-DOTA-LM3 and [177Lu]Lu-DOTA-LM3 as references. The biodistribution of [177Lu]Lu-AAZTA5-LM4 was additionally studied for the first time in a NET patient. Both [111In]In-AAZTA5-LM4 and [177Lu]Lu-AAZTA5-LM4 displayed high and selective targeting of the HEK293-SST2R tumors in mice and fast background clearance via the kidneys and the urinary system. This pattern was reproduced for [177Lu]Lu-AAZTA5-LM4 in the patient according to SPECT/CT results in a monitoring time span of 4-72 h pi. In view of the above, we may conclude that [177Lu]Lu-AAZTA5-LM4 shows promise as a therapeutic radiopharmaceutical candidate for SST2R-expressing human NETs, based on previous [68Ga]Ga-DATA5m-LM4 PET/CT, but further studies are needed to fully assess its clinical value. Furthermore, [111In]In-AAZTA5-LM4 SPECT/CT may represent a legitimate alternative diagnostic option in cases where PET/CT is not available.